DAMPAK BERDIRINYA PASAR MODERN TERHADAP PERTUMBUHAN EKONOMI (JEB17 : Jurnal Ekonomi dan Bisnis, 2017)
The study entitled "The Impact of the Establishment of Modern Market Against Economic Growth In East Java Province "it aims to know the effect of modern market on economic growth in East Java by measuring the number of modern market, population, household consumption, income and also to know the rate of growth and economic structure in East Java Province. Types and sources of data using quantitative approach with secondary data in the form of time series data observation period 2005-2014. Research variable consist of dependent variable that is economic growth (Y). Independent variables are modern market (X1) population (X2), household consumption (X3) and income (X4) and Modern Market Growth. Data analysis tools using multiple linear regression method, t test, f test and coefficient of determination (R2). Based on the results of multiple linear regression analysis obtained results as follows: Y =34.093+ 0,000 X1 + -7.932e X2 + -5.626E-7X3 + 0.000 X4. Also obtained by the modern market value of 0.898, the total population of -5,295 household consumption of -2,288 and income of 5,504 with ttable 2,262. While for testing on simultaneously obtained value Fhitung 15.712> Ftabel 5.192. Thus H0 is rejected and Ha accepted. The conclusion of this research indicates that modern market, population, household consumption and income have an effect on to economic growth in East Java Province. While the variable of population and household consumption is the most dominant variable influence in economic growth and in East Java Province. Keywords: Economic Growth of East Java, Modern Market, Population, Level Community Revenue and Consumption